ASURANSI SYARIAH DAN GAGASAN AMANDEMEN UNDANG-UNDANG NOMOR 02 TAHUN 1992 TENTANG PERASURANSIAN - hidayatulloh hidayatulloh (Universitas Lampung, 2014)
Saria Insurance has been present since 1994 with the birth of PT Syarikat Takaful Indonesia, which then established PT Asuransi Takaful Family (Life Insurance) and PT Asuransi Takaful Umum (General Insurance). That is, already 18 years Saria Insurance live, thrive and exist in the midst of the people of Indonesia. In contrast to his siblings, Islamic banking, which has had legal certainty with the Law Number 21 of 2008 concerning Islamic Banking, Islamic insurance not specifically regulated in the rule of law. Though true, Islamic principles should be applied, and Law Number 2 of 1992 on the Insurance have not been able to accommodate all the principles of sharia Islamic insurance industry in Indonesia. The presence of legislation on Islamic insurance, either by making special laws or amendments to laws existing insurance, are great expectations in order to ensure legal certainty for stakeholders and provide confidence to the public in using the products and services of Islamic insurance. Keywords: Islamic Insurance, Insurance Act, Amendment, Rule of Law.